2016
DOI: 10.1016/j.is.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Urban navigation beyond shortest route: The case of safe paths

Abstract: Advancements in mobile technology and computing have fostered the collection of a large number of civic datasets that capture the pulse of urban life. Furthermore, the open government and data initiative has led many local authorities to make these datasets publicly available, hoping to drive innovation that will further improve the quality of life for the city-dwellers. In this paper, we develop a novel application that utilizes crime data to provide safe urban navigation. Specifically, using crime data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 29 publications
0
54
0
12
Order By: Relevance
“…Rather than focusing on monetary incentives, we attempt to appeal to users by considering their characteristics and travel preferences. Recently, scholars have discovered that distance is not the only factor that humans take into consideration when preferring a route over another [17][18][19]. In fact, some studies have suggested that some individuals may even deviate up to approximately a 30% from the shortest path in exchange for a pleasant journey [20].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather than focusing on monetary incentives, we attempt to appeal to users by considering their characteristics and travel preferences. Recently, scholars have discovered that distance is not the only factor that humans take into consideration when preferring a route over another [17][18][19]. In fact, some studies have suggested that some individuals may even deviate up to approximately a 30% from the shortest path in exchange for a pleasant journey [20].…”
Section: Related Workmentioning
confidence: 99%
“…Users suggested that proposed routes were more apt for cheering up (i.e., happy route), a stressful day (i.e., quiet route), and for sightseeing (i.e., beautiful route). Later on, Galbrun et al [18] proposed an algorithm that calculates safer paths as an alternative to the shortest path. For that, the authors employ open crime data from the city of Chicago to map those city segments with the highest crime rates.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider the factors that neighbors deemed necessary in the interview, and we incorporate them as criteria for generating routes suggestions. For example, a user might want to avoid certain parts of a route based on the (in)security of the area [14], the walkability (which we define further on), the closeness to bus routes and many other factors that are not usually considered when calculating routes for users.…”
Section: Criteria For Route Selectionmentioning
confidence: 99%
“…The criterion for optimization can be chosen depending on the desired goal (minimum energy expended, minimum time, minimum torque required, or one combining these). [26][27][28] The algorithm also works for non-smooth, nondifferentiable profiles. In fact, it performs a discretization of the track, calculates the slope of the ground at the ground-wheel contacts.…”
Section: Introductionmentioning
confidence: 99%